Diversity and threats of larger mammals in montane forests of Huánuco, Peru - Aquino, Rolando (2022)
In this work, the larger mammals that inhabit the montane forests of the department of Huánuco are studied to determine the diversity of species and the status of their populations. Linear transect censuses and interviews were conducted between 2014 and 2015 on six sampling sites corresponding to five provinces. 439 records belonging to 37 species were obtained from the censuses and nocturnal explorations. Of these species, 4 are endemic to Peru and 9 are in some conservation category of Peruvian legislation. The most representative orders corresponded to carnivores and primates with 11 and 10 species, respectively, while the most frequent sightings were of Tremarctos ornatus (43 records), Nasua nasua (34 records) and Cuniculus paca (32 records). The Shannon-Wiener and Simpson Diversity Indices indicate Miraflores as the sampling site with the highest diversity (H'=3.11, 1-D=0.95). The main threat to larger mammals and other components of the larger fauna is deforestation; however, the presence of indicator species of the primary fauna community such as Tremarctos ornatus, Lagothrix flavicauda and others primates, indicate that there are still relatively extensive fragments of primary forest, particularly between the Chontayacu and Crisnejas rivers in the province of Marañón and between the Oso mayo and Blanco rivers in the province of Puerto Inca, so they must be taken into account for their conservation.